How Bacteria-Induced Apoptosis of Intestinal Epithelial Cells Contributes to Mucosal Inflammation - Martin Hausmann (Hindawi Limited, 2010)
The life cycle of an intestinal epithelial cell is terminated by apoptosis and/or cell shedding. Apoptotic deletion of epithelial cells from the intact intestinal mucosa is not accompanied by detectable inflammatory response or loss of barrier function. But increased permeability of the epithelial barrier and increased apoptotic rates of epithelial cells have been reported for patients suffering from inflammatory bowel disease. Microbiota can both induce or inhibit apoptosis of intestinal epithelial cells thus contribute to mucosal inflammation or support epithelial integrity respectively. Bacteria-mediated cytokine secretion and altered cell signalling are central to epithelial injury. Tumor necrosis factor (TNF) secreted after exposure to invasive bacteria induces both apoptosis and cell shedding. TNF is the major target gene of the transcription factor nuclear factor-kappa B with both pro- and anti-apoptotic effects. Autophagy promotes both cell survival and "autophagic" cell death. If autophagy is directed against microbes it is termed xenophagy. Inhibition of xenophagy has been shown to decrease cell survival. Endoplasmic reticulum (ER) stress causes misfolded proteins to accumulate in the ER lumen. It was suggested that ER stress and autophagy may interact within intestinal epithelial cells. Apoptosis in response to infection may be well proposed by the host to delete infected epithelial cells or could be a strategy of microbial pathogens to escape from exhausted cells to invade deeper mucosal layers for a prolonged bacterial colonization.